HUBUNGAN SELF-REGULATED LEARNING DAN BERFIKIR KRITIS DENGAN KEMAMPUAN LITERASI DIGITAL DAN LITERASI NUMERASI SEKOLAH DASAR TAHUN PELAJARAN 2024-2025 - Herawati; Cahyani, Isah; Syafruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the relationship between Self-Regulated Learning and critical thinking on digital literacy and numeracy literacy of elementary school students. The subjects of the study were 100 6th grade students from five schools in Bandung Kulon District. The canonical correlation method was used with instruments in the form of questionnaires for Self-Regulated Learning and digital literacy, as well as tests for critical thinking skills and numeracy literacy. Assumption tests include normality, linearity, non-multicollinearity, and homogeneity of variance-covariance. The results show a canonical correlation significance value of 0.000 (<0.05), which indicates a significant relationship between the variables. The first and second canonical functions are significant with p values of 0.000 and 0.02, respectively. The canonical coefficient and loading indicate that critical thinking has a dominant influence in improving numeracy literacy, while Self-Regulated Learning plays an important role in strengthening digital and numeracy literacy. This study confirms the importance of Self-Regulated Learning and critical thinking in improving student literacy and provides insight into efforts to improve literacy in the digital era